PENGARUH KEGIATAN MONTASE TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI TK TUNAS MELATI KANDIS, KABUPATEN SIAK - Santha Naibaho; Wusono Indarto; Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the results of field observations on the fine motor skills of students have not developed optimally. So it is necessary to implement the montage activity. This study aims to determine the effect of montage activity on fine motor skills of children aged 5-6 years in kindergarten Tunas Melati Kandis, Siak regency. The sample used in this study were 23 students. The data collection techniques used are observation and documentation. Data analysis technique used t-test with SPSS 20.0. The research hypothesis is that montage activity has influence to fine motor ability of age 5-6 years in Tunas Melati Kandis kindergarten. This can be known from the analysis of data obtained thitung = 26.927 and Sig. (2-tailed) = 0.000. Because Sig. (2-tailed) = 0.000 <0,05 hence it can be concluded that there is difference of motoric ability of students significantly after montage activity in learning. So it means Ho is rejected and Ha accepted which means there is a very significant difference between before and after doing experiment with applying montage activity. The influence of montage activity on fine motor ability of children aged 5-6 years in kindergarten Tunas Melati Kandis, Siak regency of 65.10%.Keywords:Fine Motoric Ability, Activity Montage